Stress as a Method of Increasing Performance and Stimulating Innovation: A Synthesis of Literature - Paresashvili Nino; Avsajanishvili Eka (Economics and Business)
Constantly changing environment, rapid pace of technological development and increased competition have a significant impact on the working environment and the psycho-emotional state of employees. Stress, a human response to unpleasant environmental factors, is one of the most common problems. It affects the physiological and psychological states, and a long-term stressful environment may even cause irreparable damage. From an organisational point of view, it affects performance, job satisfaction, motivation, social relationships, and overall success and goal achievement. The aim of the paper is to present organisational stress in a positive context, which stimulates new ideas and methods, increases performance and professionalism of employees. To explore the issue, recent literature and research papers are discussed. The main conclusion is that coping with stress depends on the management and the employee’s personality. If appropriately managed and on time, it can become a stimulator of innovation and new ways of dealing with various challenges; moreover, it can increase performance. Organisations must have pre-defined approaches and methods, as well as relevant knowledge, to respond in a timely manner and promote both employee and organisational development.